Isolation and \(in vitro\) cultivation of human urothelial cells from urine of patients - Trang, Phan Thi Kieu; Duong, Nguyen Thanh; Hoang, Nguyen Huy (Academia Journal of Biology, 2021)
In clinical practice the number of urothelial cells collected by biopsy are limited and the procedure requires general anaesthesia. Therefore, in order to acquire enough urothelial cells for in vitro engineering of the urothelium, in this research we aim to isolate urothelial cells from human urine by an alternative, effective, low-cost and safe technique rather than using the indicated method. Sixty human urine samples had been collected from patients and volunteers, cells then were precipitated by centrifugation and cultured. Following the isolation process, these cells were characterized by the immunocytochemical method using some specific antibodies. There are 2 types of cells were successfully isolated from with different shape and morphology, one of them grew randomly while the others formed smooth-edge contours and cobblestone-like cell morphology. These cells were characterized by immunostaining with a specific marker, both of these cells were positive for urothelial marker cytokeratin 7. All these results were taken into consideration, the isolated cells were urothelial cells observed in the urine-derived cell population. These results will be used for in vitro studies in toxicological and clinical research, and it will be the premised research to determine the cell mechanical properties and then develop a promising method for early diagnosis of bladder cancer.